Does Online Search Crowd Out Traditional Search and Improve Matching Efficiency? Evidence from Craigslist - Kroft, Kory; Pope, Devin G. (Journal of Labor Economics, 2014)
Since the seminal work of Stigler in 1962, economists have recognized that information is costly to acquire and leads to “search frictions.” Growth in online search has lowered the cost of information acquisition. We analyze the expansion of the website Craigslist, which allows users to post job and housing ads. Exploiting the sharp geographic and temporal variation in the availability of online search induced by Craigslist, we produce three key findings: Craigslist significantly lowered classified job advertisements in newspapers, caused a significant reduction in the apartment and house rental vacancy rate, and had no effect on the unemployment rate.